79 Physical Activity Promotion Using mHealth: A Systematic Review and Meta-synthesis of Adults' Experiences. (16th September 2019) - Carter, Daniel; Robinson, Katie; Forbes, John; Hayes, Sara
Abstract: Background: Well-documented health benefits are associated with 150 min/week of moderate-to-vigorous physical activity (PA). However, a majority of older adults do not follow this guideline and calls to address this disparity with technology have been made (1). Recommendations from the wider PA literature suggest the incorporation of mobile and wireless technology, i.e. mobile health (mHealth), into PA interventions (2). This study aims to identify and synthesise the evidence base on the experiences of adults using smartphone applications for the promotion of PA. Methods: A systematic search of CINAHL, Embase, ERIC, Medline and PsycINFO was conducted in October 2017. Primary qualitative studies with extractable data on the experiences of adults using mHealth for the promotion of PA were included. Data were analysed in NVivo using a meta-ethnographic approach. Results: The initial search yielded 4, 420 articles. After screening, fifteen articles were included, of which three included young adults, two included young and middle-aged adults, six included middle-aged and older adults and three included young, middle-aged and older adults, while one study did not report age. Because findings were not stratified by age, data were analysed collectively. Our inductive findings included the idea that end-users value the experience of personalisation offered by smartphone applications. Furthermore, mHealth raised awareness of individuals' PA level, supporting them to strategise ways of incorporating PA into their routines. Finally, negative experiences were not uncommon, though were largely caused by poor design and technical faults (e.g. battery life/ inaccurate data). Conclusion: Our review provides evidence of the paucity of studies focused on the experiences of older adults using mHealth for the promotion of PA. Given recommendations for PA interventions to be tailored, particularly across the lifespan (2), and the positive findings noted in the current study, further primary qualitative studies exploring the perspectives of older adults are warranted.